Antioxidant Capacity and Phenolics Profile of Portuguese Traditional Cultivars of Apples and Pears and Their By-Products - Teixeira, João David (2023)
Funding Information: This research was funded by the clabel+ project: Innovative Natural, Nutritious and Consumer Oriented “Clean Label” Foods with the reference POCI-01-0247-FEDER-046080 financed by the Competitiveness and Internationalization Thematic Operational Programme (PO CI), under the COMPETE2020, PORTUGAL2020 Partnership Agreement, through the co-financing of European Regional Development Fund (FEDER). J.D. Teixeira is grateful for his fellowship in the frame of clabel+ project. The work was supported by UIDB/00211/2020, LA/P/0045/2020 (ALiCE), UIDB/00511/2020 and UIDP/00511/2020 (LEPABE), UIDB/04551/2020 (GREEN-IT—Bioresources for Sustainability) funded by national funds through FCT/MCTES, UIDB/04469/2020 (CEB) and by LA/P/0029/2020 (LABBELS), Centre of Chemistry (UID/QUI/0686/2020) and project BioTecNorte (operation NORTE-01-0145-FEDER-000004), supported by the Northern Portugal Regional Operational Programme (NORTE 2020), under the Portugal 2020 Partnership Agreement, through the European Regional Development Fund (ERDF). Publisher Copyright: © 2023 by the authors.